Analisis bibliometrik tren penelitian human rights dalam lingkup e-commerce di Indonesia - Maulana, Muhammad Asrul; Aristi, Savira (Jurnal Informatio, 2025)
Human rights in e-commerce demand a legal system capable of providing simultaneous and comprehensive protection to consumers. In the digital age, consumers face various risks, such as personal data theft, algorithm manipulation, and unequal access to digital services. Therefore, scientific studies on this issue are crucial in encouraging the development of responsive and inclusive policies. Bibliometric analysis of previous research aims to provide in-depth insights into the development of this theme. Additionally, this analysis can help identify the main contributions of researchers and discover research gaps that can be filled to further develop knowledge. This research aims to identify global research patterns, major themes, and new opportunities that can support the development of a more effective and adaptive legal system in the face of digital age challenges. This study employs a mixed-methods approach, utilizing quantitative methods for bibliometric analysis of lens.org search metadata and qualitative methods through comparisons with Supreme Court decisions. The results show a significant increase in the number of publications in this field since 2005, peaking in 2017. This reflects the growing attention to consumer rights issues in e-commerce. The most productive country in this research is the United Kingdom with 3,395 journals, while the institution with the largest contribution is the University of Edinburgh. Furthermore, a research gap was identified regarding the development of a global legal framework that is adaptive to the challenges of the digital age. These findings guide researchers and policymakers to direct future research and formulate comprehensive policies to protect consumer rights in e-commerce.